Pengaruh Manajemen Kinerja, Antusiasme, Motivasi, dan Pelatihan terhadap Kepuasan Kerja Karyawan pada Badan Usaha Milik Negara (BUMN) - Adriand Bagus Sopyan Nanda,; Jatmiko Jatmiko, (Manajemen Kreatif Jurnal, 2024)
Job satisfaction has the potential to increase company productivity and emphasizes the importance of developing concepts to measure human resources. Each individual has varying levels of job satisfaction, influenced by the values they hold and their unique characteristics. Satisfaction is also related to the extent to which individuals feel their needs, wants and aspirations are met, which ultimately depends on the goals they want to achieve in their lives. The purpose of this study is to determine the relationship between the variables of Performance Management, Enthusiasm, Motivation, and Training to Employee Job Satisfaction simultaneously and partially. This research is a deductive type of research using quantitative methods. The sample in this study amounted to 145 respondents using data collection techniques using purposive sumpling. Then the data is processed using multiple linear regression analysis methods using SPSS. Based on the test results, it is known that the variables of performance management, enthusiasm, motivation, and training simultaneously and partially have a positive effect on job satisfaction.